From Tweets to Tension: How Language Shape Hoaxes and Hatred in the Twitterverse - Daulay, Sholihatul Hamidah; Rizky, Fitri Miftahul; Lubis, Rodiatul Audiyah (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
Language is a primary tool for human communication, and influencing the thoughts and behaviors of others. In the context of social media platforms such as Twitter, language plays a highly strategic role, not only as a medium for personal expression but also as a powerful channel for the wide dissemination of information. One of the most concerning misuses of language in this sphere is the spread of hoaxes false or misleading information that is deliberately constructed to appear truthful, often with specific intentions such as deception, provocation, or incitement of division. This article examines how language is employed to construct and reinforce the narratives of hoaxes and hate speech on Twitter, focusing on lexical choices, rhetorical style, and the emotional appeals embedded in the language. often provocative, manipulative, and designed to elicit strong emotional reactions from audiences. It reveals that hoaxes and hate speech on social media frequently utilize linguistic techniques such as excessive generalizations and inflammatory diction to create tension and sow division within society. The impact of such phenomena extends beyond the digital realm, potentially triggering real-world social conflicts. Through a linguistic and media studies approach, this article aims to uncover the patterns of language used in the dissemination of disinformation and hate, while encouraging readers to adopt a more critical, mindful, and responsible attitude toward language use on social media platforms.